TERRACLASS DIGITAL PLATFORM FOR ANALYSIS OF THE DYNAMICS OF LAND USE AND LAND COVER IN THE UPPER PARAGUAY BASIN - Gonçalves Antunes, João Francisco; dos Santos, João Luís; Sanches Bertolo, Lídia; Pedroso Curtarelli, Victor; Calaboni, Adriane; Camargo Coutinho, Alexandre; Dalla Mora Esquerdo, Júlio César (Ra’e Ga: o Espaço Geográfico em Análise, 2025)
The Upper Paraguay Basin (BAP, Portuguese acronym) is an ecosystem of strategic importance to Brazil because it includes the Pantanal, one of the world’s largest floodplains. The wet plain is well preserved, but the plateau suffered the impact of anthropic activities on the natural resources, due to the rapid conversion of vegetation cover in recent decades. Therefore, it is essential to investigate land use and cover changes to define strategies that stimulate environmental conservation and regional development. The BAP plateau region is covered by the mappings of the TerraClass Project, which provides official data for monitoring land use and cover in the Amazon and Cerrado biomes. In this context, the objective of the work was to analyze changes in land use and land cover in municipalities of the BAP, using the modern GeoPortal TerraClass and the recent data collection from 2018, 2020, and 2022. The spatial analysis showed that the native forest loss occurred due to increased deforestation. Most of the forest regeneration areas persisted during this period, and the lost area was converted into pastures, where agriculture expanded, initially with one cycle production, followed by the intensification of crop and off-season production. The results demonstrate the potential of the data and tools offered by the Digital Platform TerraClass to support territorial management.